Critical Thinking Skills among Final Year Students of Malaysian Technical Universities - Aziz , Yahya; Safiah , Sidek; Zanariah , Jano (2011)
Critical thinking is an essential skill that individuals need to have in order to be effective learners and workers in the global knowledge economy. In line with the mandate of the Ministry of Higher Education Malaysia (MOHE), institutions of higher learning including universities under the Malaysian Technical Universities Network (MTUN) have adopted several approaches to ensure that their graduates are equipped with the sufficient level of critical thinking skills. However, there is little knowledge about the attainment levels of critical thinking skills, among Malaysian tertiary students. Thus, the California Critical Thinking Skill Test (CCTST) was used to collect data from one hundred final year students at four Malaysian Technical Universities in order to identify their attainment level on critical thinking skills. The CCTST scores revealed that these students exhibit some proficiency in critical thinking, but they are way behind the global standard, as stipulated by Insight Assessment California. Students’ competencies of the CTS also vary across the four universities. This study has significant implications on the curriculum design and development as well as pedagogical practice adopted by MTUN universities in developing their students with appropriate level of critical thinking skills.